Going Too Far Is the Same as Falling Short†: Kinesin-3 Family Members in Hereditary Spastic Paraplegia - Gabrych, Dominik R.; Lau, Victor Z.; Niwa, Shinsuke; Silverman, Michael A. (Frontiers in Cellular Neuroscience, 2019)
Proper intracellular trafficking is essential for neuronal development and function, and when any aspect of this process is dysregulated, the resulting “transportopathy” causes neurological disorders. Hereditary spastic paraplegias (HSPs) are a family of such diseases attributed to over 80 spastic gait genes (SPG), specifically characterized by lower extremity spasticity and weakness. Multiple genes in the trafficking pathway such as those relating to microtubule structure and function and organelle biogenesis are representative disease loci. Microtubule motor proteins, or kinesins, are also causal in HSP, specifically mutations in Kinesin-I/KIF5A (SPG10) and two kinesin-3 family members; KIF1A (SPG30) and KIF1C (SPG58). KIF1A is a motor enriched in neurons, and involved in the anterograde transport of a variety of vesicles that contribute to pre- and post-synaptic assembly, autophagic processes, and neuron survival. KIF1C is ubiquitously expressed and, in addition to anterograde cargo transport, also functions in retrograde transport between the Golgi and the endoplasmic reticulum. Only a handful of KIF1C cargos have been identified; however, many have crucial roles such as neuronal differentiation, outgrowth, plasticity and survival. HSP-related kinesin-3 mutants are characterized mainly as loss-of-function resulting in deficits in motility, regulation, and cargo binding. Gain-of-function mutants are also seen, and are characterized by increased microtubule-on rates and hypermotility. Both sets of mutations ultimately result in misdelivery of critical cargos within the neuron. This likely leads to deleterious cell biological cascades that likely underlie or contribute to HSP clinical pathology and ultimately, symptomology. Due to the paucity of histopathological or cell biological data assessing perturbations in cargo localization, it has been difficult to positively link these mutations to the outcomes seen in HSPs. Ultimately, the goal of this review is to encourage future academic and clinical efforts to focus on “transportopathies” through a cargo-centric lens.